Ocena znaczenia jakości państwa - Piotrowska, Maria (How is governance important?, 2006)
The paper addresses the problem whether improvement of governance should be one of main tasks for the Polish government? Results obtained for the EU countries show the significance of governance for the size of a country and the efficiency of accomplishment of two main goals: redistribution and stimulating of economic growth. Considering them, low efficiency of government institutions and quality of law in Poland should encourage Polish authorities to make significant improvements. The verification of research hypothesis is based on the regression estimations for a sample of 24 European countries between 1996 and 2004.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1131, s. 217-229